Biodistribution studies of boronophenylalanine in different types of skin melanoma. (September 2020) - Zhang, Zizhu; Yong, Zhong; Jin, Congjun; Song, Zewen; Zhu, Shaihong; Liu, Tong; Chen, Yang; Chong, Yizheng; Chen, Xinru; Zhou, Yongmao
Abstract: A study of the 10 B-enriched Boronophenylalanine-fructose complex( 10 BPA-F) infusion procedure in potential BNCT patients, including three skin melanomas of extremities, was performed. 10 B concentration in tumor(T), blood(B), skin(S) were measured to determine tumor/blood(T/B) and skin/blood(S/B) ratios. T/B ratio for three melanoma patients was in the range 1.48-3.82(average 2.56 ± 0.69). S/B ratio was in the range 0.81-1.99(average 1.29 ± 0.35). Results showed that T/B ratio of nodular metastasis melanoma was higher than superficial spreading melanoma. 10 B concentration in skin was higher than blood, which was helpful to avoid over-dose in normal skin. Highlights: Biodistribution studies of boronophenylalanine-fructose complex in different types of skin melanoma. 10 B concentration in tumor(T), blood(B), skin(S) were measured to determine tumor/blood(T/B) and skin/blood(S/B) ratios. T/B ratio of nodular metastasis melanoma was higher than superficial spreading melanoma. 10 B concentration in skin was higher than blood, which was meaningful for dose control of normal skin.